Epidemiological Profile of Skin Diseases in a Tertiary Hospital of Kathmandu: An Annual Census - Paudel, Sushil; Sharma, Rabindra; Dahal, Sudip; Acharya Paudel, Indu (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
Introduction: Skin diseases are eighth most common reasons for outpatient in Nepal, and fourth cause of disability globally. Skin diseases varies with the reason, season and socioeconomic status. As the socioeconomic conditions are changing, so are the disease patterns. We planned to report the current trend of skin diseases in Kathmandu and compare with similar studies in past. Materials and methods: Outpatient department records of Civil Service Hospital from the year 2075 Bikram Sambat were reviewed after ethical clearance from institution review committee and were analyzed after tabulation. Results: Total number of cases were 9886 (4.51% of total hospital attendance). In total 8097 cases were new, males were 4218 (52.1%) and females 3879 (47.9%). Most common diagnosis was eczemas (18.47%), followed by dermatophytosis (15.29%). Eczemas, chronic urticaria, psoriasis and lichen planus were more common in the adult population of more than 30 years. While infections and acne were more common in young adults, 15-30 years, in both the sexes. Tinea was common during summer and so was scabies in males, while in females, melasma peaked in summer and chronic urticaria during spring and winter. Conclusion: The pattern of skin diseases is changing with the time. Diseases of possible allergic and immunologic etiology are increasing and diseases with infective etiology are still a huge burden on society.